Sleep And Hba1c In Adult Patients With Type 2 Diabetes Mellitus - Rizki Andriani; Orita Satria; Nurhadia Nurhadia; Crasdian Afri Yudi (Universitas Muhammadiyah Surakarta, 2023)
Sleep is one of the essential factors in life and affects glucose metabolism, so it is crucial for diabetic patients to have good quality sleep to control their diabetes. The study aimed to analyze the relationship between sleep quality and HbA1c levels in adult patients with type 2 diabetes mellitus. This study was conducted with a cross-sectional study approach with a sample of 170 respondents with convenience sampling from a hospital in Banda Aceh. Sleep quality data was measured by the Pittsburgh Sleep Quality Index (PSQI), and HbA1c levels were obtained from the results of respondents' HbA1c examinations in the last three months analyzed through chi-square. The results showed a significant relationship between sleep quality and respondents' HbA1c levels (p = 0.008), where respondents (64.1%) with poor sleep quality had an eight times the risk of having uncontrolled HbA1c levels compared to respondents with good sleep quality. Education on the importance of sleep health in patients regularly should be carried out in groups by health services to motivate T2DM patients to enjoy adequate sleep and improve their glycemic control through learning media that interest patients